Face Detection and Recognition using Machine Learning Techniques - Vijayalakshmi, S.; Maheswari, J. Uma; Jananiyie, K. (Journal of Innovative Image Processing, 2023)
Face recognition of persons has received so much attention in the recent years due to its many applications in different fields such as security applications, video surveillance, biometric systems, identifying the criminals etc. This paper develops a system that can recognize the human face in the input image after it has been detected. The system is trained with set of faces and non faces, and when the input picture is given, the face is detected using Viola Jones Algorithm. In face recognition, the features are extracted from the training dataset using Principal Component Analysis (PCA) and then the system is trained to recognize the face using Support Vector Machine (SVM) classification. When the input image is given for face recognition, features are extracted from the input picture using PCA and multiclass classification is done by SVM.
Keywords: Multiclass classification; support vector machine; principal component analysis; viola jones algorithm